Features of using the structural damping in construction of cutting tools - Novitskyi, Yurii (Lviv Polytechnic Publishing House, 2015)
The influence of internal friction parameters in the joints of structural elements on the machine for vibration amplitude of cutting tool and detail was analyzed. The possibility of effectively suppress the amplitude of oscillation of the cutting tool by selecting optimal parameters of frictional connection of the cutting blade was shown.
Keywords: structural damping; cutting tools; oscillations; amplitude; resonance; friction